Src Homology 2 Domain-Containing Protein Tyrosine Phosphatase Promotes Inflammation and Accelerates Osteoarthritis by Activating β-Catenin - Tao, Tenghui; Luo, Danni; Gao, Chenghao; Liu, Hui; Lei, Zehua; Liu, Wenbin; Zhou, Chuankun; Qi, Dahu; Deng, Zhenhan; Sun, Xuying; Xiao, Jun (Frontiers in Cell and Developmental Biology, 2021)
Osteoarthritis (OA) is a chronic articular disease characterized by cartilage degradation, subchondral bone remodeling and osteophyte formation. Src homology 2 domain-containing protein tyrosine phosphatase (SHP2) has not been fully investigated in the pathogenesis of OA. In this study, we found that SHP2 expression was significantly increased after interleukin-1β (IL-1β) treatment in primary mouse chondrocytes. Inhibition of SHP2 using siRNA reduced MMP3, MMP13 levels, but increased AGGRECAN, COL2A1, SOX9 expression in vitro. On the contrary, overexpression of SHP2 exerted the opposite results and promoted cartilage degradation. Mechanistically, SHP2 activated Wnt/β-catenin signaling possibly through directly binding to β-catenin. SHP2 also induced inflammation through activating Mitogen-activated protein kinase (MAPK) and nuclear factor κB (NF-κB) pathways. Our in vivo studies showed that SHP2 knockdown effectively delayed cartilage destruction and reduced osteophyte formation in the mouse model of OA induced by destabilization of the medial meniscus (DMM). Altogether, our study identifies that SHP2 is a novel and potential therapeutic target of OA.